2023
DOI: 10.2147/ndt.s387362
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students Facilitating the Transition from Suicidal Ideation to Action in the Rural: A Qualitative Study

Abstract: Objective This study aims to increase understanding of the process of nursing students at risk of completing suicide attempts that facilitates the transition from suicidal ideation to action. And The Central Bureau of Statistics, there were 812 suicide cases throughout Indonesia. Methods The qualitative research involved 15 nursing students who were selected purposively. data collection in rural East Java Data were collected through semi-structured interviews and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For this reason, it is important for nurses to have good knowledge and understanding of the clinical symptoms that arise so that they are able to treat patients with proper management. 31 Another theme in this study reports about the majority of cases of Covid-19 transmission that occurred in school clusters. Although some research evidence suggests that school-age children are less likely to be infected with Covid-19, 32,33 and a case study by 34 also reports that no there is transmission from a child infected with Covid-19 despite contact with more than a hundred children at school, but the prognosis is different for children who are infected with Covid-19 and have a history of comorbid diseases.…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, it is important for nurses to have good knowledge and understanding of the clinical symptoms that arise so that they are able to treat patients with proper management. 31 Another theme in this study reports about the majority of cases of Covid-19 transmission that occurred in school clusters. Although some research evidence suggests that school-age children are less likely to be infected with Covid-19, 32,33 and a case study by 34 also reports that no there is transmission from a child infected with Covid-19 despite contact with more than a hundred children at school, but the prognosis is different for children who are infected with Covid-19 and have a history of comorbid diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research found that fantasy/natural conditions in the field are the main ingredients of fun learning. 25 We saw several cases of natural conditions in the field that became the main attraction during this learning method. 34 The most critical challenge most students face in higher education is the cognitive challenge—challenges in their learning.…”
Section: Discussionmentioning
confidence: 99%
“…14 Observes that social presence "develops interpersonal skills but may not be required to synthesize knowledge", 24 a feature that may be regarded positively in terms of nursing research education. 25 While some students, particularly those who participated in the interviews, expressed a sense of community, active inquiry, and connectedness, others expressed discomfort communicating openly in live online learning circle sessions and blogs, a factor related to 26 Collaboration skills development is becoming more essential in the current world and contemporary research community. 27 Nurse researchers must be both collaborative and critical thinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of domestic studies in the field of mental health caregiving, we evaluated international studies and found that 18 out of 20 problems could be solved by improving communication between caregivers [18] . Yunitasari compiled a list of the stresses experienced by mental health caregivers in the community and hospitals with emergency patients, based on findings from studies performed in various countries and published in academic journals [19] . There was a correlation between the organizational, environmental, and professional difficulties experienced by caregivers [20] in acute admittance hospitals and caregivers in the community mental health setting (CMHN).…”
Section: Discussionmentioning
confidence: 99%